Nursing and immunization for immunodepressed patients related to malignant neoplasia (Research, Society and Development, 2021)
Introduction: Immunization is a measure of prevention and control for certain diseases, and under normal conditions, the cells of the human body are able to respond to numerous infectious or antigenic stimuli, in addition to vaccination. Objective: to describe the particular aspects of immunization in patients undergoing cancer treatment. Methodology: Integrative review study. The analysis was carried out after applying the inclusion and exclusion criteria, and a database was built covering the items title, year of publication, periodical, CAPES qualis, study design, scenarios and country. Results: 24 articles were analyzed, 58.3% without qualification classification, and in the others, frequency of qualifications in A2 (60.0%). The study design concentrated 54.1% at level 02 of scientific evidence. The vaccines described in the studies were a total of 11, with emphasis on Influenza with an occurrence of 83.3%. For seroconversion, the positive result was 31.9% (15/47). Final Considerations: It is concluded that the productions are concentrated in a high level of scientific evidence, denoting experiments for the application of attenuated vaccines in patients immunocompromised by malignant neoplasms.